2023
DOI: 10.1371/journal.pone.0282875
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology predicts combinational effect of novel herbal pair consist of Ephedrae herba and Coicis semen on adipogenesis in 3T3-L1 cells

Abstract: Background Herbal combinations are regarded as basic strategy in oriental medicine with various purposes. Ephedrae herba (EH) and Coicis semen (CS) are two herbal medicines used to treat obesity in many herbal prescriptions, yet the effect and significance of this herbal pair have not been evaluated. Purpose This study is to elucidate the effect of a novel herbal pair, EH-CS, on obesity and identify the key synergistic mechanism underlying it. Methods We investigated the network of herbs comprising the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…On the other hand, several studies have reported the anti-obesity e cacy of CS. However, the reported mechanism was different from that of EH 24 .…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…On the other hand, several studies have reported the anti-obesity e cacy of CS. However, the reported mechanism was different from that of EH 24 .…”
Section: Introductionmentioning
confidence: 83%
“…We hypothesized that some compounds in CS may enhance the pharmacological effect of EH. Hence, we tested the effects of two compounds of CS, identi ed in a previous study, on EH-treated adipocytes 24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations